Malkom Khan’s thought on political modernization in Iran - Shahriari, Kamyab (2016)
This research studied the subject of Malkom Khan's Thoughts on Political Modernization in Iran. The objectives of this study are to evaluate Malkom Khan's ideas toward political modernization in the first and second period of his thoughts (1857-1908) and to assess reasons that led to a change in Malkom Khan's political thoughts on political modernization. To do this research, the biographical method was used to analyze data collected during the whole period of the research. As a biographic research, this research was conducted by using both the primary and secondary data together. The primary data in this research was obtained from Malkom Khan‟s books and documents (letters, correspondence and reports) and the secondary data was obtained from books, articles and critiques written by other researchers. In this research, the theory of political modernization was used to analyze Malkom Khan‟s political thoughts on modernization. As a political scholar Malkom Khan, introduced a modernization program in the framework of Saltanate Motlagheye Montazem (Law-based Absolute Monarchy) in his first period of his endeavors in order to modernize the structure of government. This method can be named as top-down political modernization and here, he paid more attention on modernization of political structure and his main goal was creation of modern and new structure. In fact, this type of government Malkom tried to establish was a government based on the concept of nation-state, although his approach to nation-state was focused predominantly on state building. However, a number of historical and personal events during Malkom Khan‟s life occurred later which led him to change his initial ideas and he adopted a bottom-up political modernization course. These events were: Lottery affairs and Malkom Khan‟s subsequent dismissal, the Tobacco Movement, and failure of Sepahsalar‟s reform. In the second period, Malkom‟s idea changed and he introduced parliamentary constitutional monarchy and proposed separation of powers in order to limit the power of the king and national consultative assembly; his main goal on political modernization during this period was nation - building by bottom-up political modernization from bottom-up. Additionally, Malkom Khan during this period of modernization of political structure also paid attention to modernization of political culture and also the religious and cultural aspects of society. Malkom Khan in the second period of his political thought and activity realized the important role of religion and religious culture of the people and found it imperative to take into due consideration the religious culture of the people in order to promote his thoughts. He concluded that no bottom-up modernization plan would be successful unless he could reconcile modern and Western thoughts with Islamic beliefs and thoughts. Therefore, he attempted in his writings to bring evidences from the hadith and Quran to achieve this reconciliation, and attempted to illustrate that there was no contradiction between Islam and modern and Western thoughts. This was to prevent possible opposition from the clergy and conservatives to his thoughts and also in order to attract the support of the progressive class of clergymen with his political modernization thoughts, which were developed on the basis of parliamentary constitutional monarchy.